2015
DOI: 10.1063/1.4919909
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces and internal layers in a turbulent boundary layer

Abstract: New experimental research is presented on the characteristics of interfaces and internal shear layers that are present in a turbulent boundary layer (TBL). The turbulent/non-turbulent (T/NT) interface at the outer boundary of the TBL shows the presence of a finite jump in streamwise velocity and is characterised by a thin shear layer. It appears that similar layers of high shear occur also within the TBL which separate regions of almost uniform momentum. It turns out that they exhibit similar characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
120
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(161 citation statements)
references
References 45 publications
38
120
2
Order By: Relevance
“…A spate of more recent investigations [18,19] has confirmed and further quantified the basic conception of UMZs advanced in the pioneering study by Meinhart & Adrian [17]; see figure 1a,b, which is adapted from de Silva et al [19]. These latter authors also show that the number of UMZs (and VFs) increases logarithmically with increasing Reynolds number.…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…A spate of more recent investigations [18,19] has confirmed and further quantified the basic conception of UMZs advanced in the pioneering study by Meinhart & Adrian [17]; see figure 1a,b, which is adapted from de Silva et al [19]. These latter authors also show that the number of UMZs (and VFs) increases logarithmically with increasing Reynolds number.…”
Section: Introductionsupporting
confidence: 49%
“…The body force per unit mass f = f (y)ê x , whereê x is a unit vector in the x-direction, is included to drive the required background (laminar) shear flow that would exist in the absence of the turbulent motions. We choose a local Cartesian coordinate system moving with the presumed planar VF (a geometrical configuration perhaps more likely to be relevant to VFs in fully developed internal flows, such as plane Poiseuille flow; see Eisma et al [18]), which is taken to be coincident with the plane y = 0. The fissure, or internal shear layer, has O( ) dimensionless thickness, where (Re) → 0 as Re → ∞.…”
Section: Large Reynolds Number Analysismentioning
confidence: 99%
“…For TBLs, Priyadarshana et al [51] investigated the event durations of intense vorticity using temporal data and concluded that the local Taylor time scale is a characteristic scale for these events [55]. Recently, Eisma et al [54] observed from spatial data that the thickness of internal interfaces in a TBL scales with the local Taylor microscale and equals approximately 0.4λ T . Note that this spatial interface thickness is in line with the values reported from the temporal studies [51,55], since Taylor's hypothesis is reasonably accurate in the centre of the log-region (note that orientation of the interface also plays a role in the observed thickness).…”
Section: Discussion and Conclusion (A) Near-wall Modulation Of Small mentioning
confidence: 99%
“…2 of Ref. [21]). We determine that the observed deviations of the wave velocities of momentum sources and sinks from the mean streamwise velocities cannot be explained as potential fluid at U ∞ contributing to the mean velocity profile.…”
Section: Resultsmentioning
confidence: 99%
“…According to this, large-scale regions of approximately uniform streamwise momentum 054601-2 are surrounded by elongated "fissures" of highly vortical flow. Later observations based on particle image velocimetry (PIV) confirmed and highlighted the importance of this interpretation [21,22].…”
Section: Introductionmentioning
confidence: 89%